Steg-o-normous - Griffin, Adele (Griffin, Adele. Oodlethunks., 2016)
"Now that Oona's dino-baby has hatched from its egg, things have gotten even wackier! Stacy the enormous stegosaurus, can't wait to explore her new world. And Oona can't wait to show her off. But not everyone's ready for this big bundle of joy whose having the time of her life romping and chomping through West Woggle. With Bonk, Bruce Brute, Erma, and even the mean witch, Old Brouhaha, on the case, this loveable babe finds her right place in the hearts of these Stone-Age folks who come to depend on this Stacy Steg to save them from some prehistoric perils" --